Proceedings Of International Conference Building Services And Energy Efficiency. Modernizing and increasing performance of Building Services - Vasilică, Ciocan (De Gruyter, 2020)
The Building Services and Energy Efficiency (BSEE) Conference is an event that has become traditional in the world of civil engineering, since 1990. The main organizer is the Gheorghe Asachi Technical University of Iasi, Faculty of Civil Engineering and Building Services. Every year, the conference presents issues of new scientific research as well as the companies' needs for creating new organizational solutions. The BSEE Conference covers all scientific and technological aspects of civil engineering and building services field: energy efficiency, building services, computer-aided design, and engineering, computational fluid dynamics, building services performance analysis, building services monitoring and management, heat and mass transfer, lighting systems, energy storage, renewable energy, enhancing sustainability and resilience of building services, numerical analysis in civil engineering, BIM. The building services and equipment have become essential elements in the construction of buildings to ensure the conditions of interior comfort. In a fast-evolving society, information is an essential element for the progress of economic-social activities, and the Conference of Building Services and Energy Efficiency represent the place where the exchange of information and ideas for the sustainable development of the built environment and its facilities takes place. The BSEE Conference accepts review articles, original scientific articles, and cases from the field of civil engineering and building services - mechanical engineering, electrical engineering, and materials. All papers in BSEE Conference are first peer-reviewed and only accepted articles that have not yet appeared in a printed or electronic issue are published.